The Effectiveness of a Caregiver Support and Education Intervention Designed for Caregivers of Veterans. (17th December 2021) - Mavandadi, Shahrzad; Eaker, April; Van Treese, Katherine; Jeffries-Silmon, Brenda; Wray, Laura
Abstract: Veterans are at increased risk for dementia and multiple comorbid conditions, often making the family caregiving experience particularly challenging. The objective of this study was to examine the effectiveness of a telephone-based, collaborative dementia care program for improving caregiver (CG) outcomes in CGs of veterans with dementia. All CGs (n=107) received individual care management and were randomized to either individual intervention alone or individual plus group education and social support. CGs were on average 72.5 (+/-11.0) years old, and the majority were female, spouses/partners of the care recipient (CR), and providing care for ≥1 year. Pre-post analyses indicate that CGs experienced a significant reduction in both the frequency of CRs' dementia-related symptoms (e.g. memory difficulties, disruptive behaviors, depressive affect) and their own distress in response to these symptoms. Our study adds to the literature on the development and evaluation of understudied CG populations, such as CGs of veterans with dementia.